Self-reflexiveness in Photo-film Form as Illustrated by Zbigniew Czapla’s "Paper Box" - Sulejewska, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article interprets Paper Box by Zbigniew Czapla as an example of iconographic film and suggests that the genre be renamed photo-film. An analysis of particular means of film expression and photographic metaphors leads to seeing photo-film as a synthesis of various media, going beyond the world of cinema in terms of genealogy.